2021
DOI: 10.1088/1755-1315/892/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil industry towards Sustainable Development Goals (SDGs) achievements

Abstract: Gender Equality in Sustainable Development Goals (SDGs) has been exclusively developed but, most of our current economies and societies are not able to fully contribute or equally benefit from them. When zooming in, women are generally more excluded than men. Indonesia as the leading of palm oil producing country and given the vital role that women and girls play in the management, care, and use of Palm Oil, the Gender Equality and Social Inclusion (GESI) framework is important to review. This paper aims to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…A and E also contributing to SDG 3 (Hariyadi, 2010;Zeba et al, 2006), and gender equality (Mardiharini et al, 2021). The palm oil industry creates many direct and indirect jobs (SDG 8), contributes to boosting socio-economic development and reducing inequalities (SDG 10), and also helps mitigate climate change (SDG 13) since it uses less land compared to other vegetable oil crops due to its high yield per ha.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A and E also contributing to SDG 3 (Hariyadi, 2010;Zeba et al, 2006), and gender equality (Mardiharini et al, 2021). The palm oil industry creates many direct and indirect jobs (SDG 8), contributes to boosting socio-economic development and reducing inequalities (SDG 10), and also helps mitigate climate change (SDG 13) since it uses less land compared to other vegetable oil crops due to its high yield per ha.…”
Section: Discussionmentioning
confidence: 99%
“…When smallholder farmers live close to agro‐industrial company mills, their families benefit from improved access to health and educational facilities that contribute to SDGs (3 and 4; Schröder et al, 2020). Palm oil is a food source rich in energy, fatty acid, vitamins A and E also contributing to SDG 3 (Hariyadi, 2010; Zeba et al, 2006), and gender equality (Mardiharini et al, 2021). The palm oil industry creates many direct and indirect jobs (SDG 8), contributes to boosting socio‐economic development and reducing inequalities (SDG 10), and also helps mitigate climate change (SDG 13) since it uses less land compared to other vegetable oil crops due to its high yield per ha.…”
Section: Discussionmentioning
confidence: 99%
“…Another article written by Sukiyono et al [49] observed that the SDGs indicators developed by the Indonesian government contain 13 points and 47 indicators suitable for smallholder plantations, where smallholders can contribute to social pillars at SDGs 1, 2, 3, 4, 5, 6 and 7 (affordable and clean energy); the economic pillar at SDGs 7, 8, 9 (industry, innovation, and infrastructure), 10 and 17 (partnerships for the goals), as well as; the environment pillar at SDGs 6, 13 and 15 (life on land). By seeing the gender aspect of palm oil plantation activities (SDG 5), Mardiharini et al [50] later found that most women are involved in doing clerical work and supporting their spouses to earn higher incomes -although women are increasingly taking leadership roles in some smallholder groups.…”
Section: Rspo Certification Contribution To Sdgs Achievementmentioning
confidence: 99%
“…Jadi penduduk miskin merupakan penduduk yang memiliki rata-rata pengeluaran perkapita untuk kebutuhan pokok dalam setiap bulannya berada dibawah garis kemiskinan. Kelapa sawit juga memiliki peran penting dalam mencapai tujuan pembangunan berkelanjutan (Mardiharini et al, 2021). Industri kelapa sawit di Indonesia memiliki pendekatan yang mengutamakan keseimbangan antara aspek ekonomi, sosial, dan lingkungan.…”
unclassified